2011
DOI: 10.2169/internalmedicine.50.4973
|View full text |Cite
|
Sign up to set email alerts
|

A Decrease in the Dose of Pegvisomant was Needed for the Treatment of Acromegaly after Adrenalectomy in a Patient with Coexisting Preclinical Cushing's Syndrome

Abstract: We herein describe the case of a 47-year-old woman with pre-clinical Cushing's syndrome caused by a left adrenal adenoma, which was diagnosed 6 years after trans-sphenoidal selective removal of a pituitary adenoma for acromegaly at age 35. The patient was started on bromocriptine and then somatostatin analogues after the surgery; however, since her serum insulin-like growth factor-1 (IGF-1) values remained above the age-adjusted normal range, the treatment for acromegaly was switched from somatostatin analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Subsequently, the authors followed nine of the 27 patients for one year and identified one patient with subclinical hypercortisolism who exhibited an increase in the size of the adrenal mass, similar to that noted in our case (8,9). To our knowledge, other than the above-mentioned case reported by Scaroni et al and our current case, only three cases of acromegaly accompanied by adrenocorticotropic hormone-independent subclinical Cushing's syndrome have been reported (10)(11)(12). No other forms of endocrinological neoplasia were observed in any of the previously reported four cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Subsequently, the authors followed nine of the 27 patients for one year and identified one patient with subclinical hypercortisolism who exhibited an increase in the size of the adrenal mass, similar to that noted in our case (8,9). To our knowledge, other than the above-mentioned case reported by Scaroni et al and our current case, only three cases of acromegaly accompanied by adrenocorticotropic hormone-independent subclinical Cushing's syndrome have been reported (10)(11)(12). No other forms of endocrinological neoplasia were observed in any of the previously reported four cases.…”
Section: Discussionsupporting
confidence: 82%
“…Previous clinical studies assessing the associations between adrenal gland tumors and acromegaly have reported correlations between a larger tumor size (11) and an increased prevalence of adenoma or hyperplasia (7,12) as well as acromegaly. However, it remains controversial whether there is a causal relationship between adrenal morphological alterations and the disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between insulin resistance and diabetic status were previously described in two of the five patients with acromegaly and Cushing's syndrome (7,10). In one patient, adrenalectomy and pituitary surgery improved the patient's insulin resistance and glucose control state (10).…”
Section: Discussionmentioning
confidence: 78%
“…That patient, however, did not demonstrate marked alterations in the treatment of diabetes, such as the discontinuation of insulin or a dramatic improvement of glucose control. The second patient was not diabetic before left adrenalectomy (7). Reports on the other three patients with acromegaly and Cushing's syndrome did not mention the glucose control status (8,9,11).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation